NATURAL FREQUENCY ANALYSIS OF SINGLE ROTOR SYSTEM WITH MODEL UNCERTAINTY (MT) - ZHANG RuiFeng; LIU BaoGuo; LIU YanXu; FENG Wei (Jixie qiangdu)
In order to study the effects of parameter approximation and modeling errors caused by lack of cognition on the natural frequency of a single-rotor system respectively, the Riccati transfer matrix method and non-parametric method was applicated to calculate the natural frequency of the rotor system with uncertainty. The contribution of various parameter uncertainties such as support stiffness, shaft length, joint mass and elastic modulus and model uncertainty to the natural frequency of rotor system was analyzed. The results show that for the natural frequency of the uncertain rotor system, the influence range of model uncertainty and parameter uncertainty is quite different, and the magnitude of the fluctuation caused by the uncertainty of different parameters is also different. The research has theoretical reference for the study of uncertain dynamics of steady-state and transient unbalanced responses.